Prognostic Value of “Cycle Threshold” in Confirmed COVID-19 Patients - Rajyalakshmi, B (Indian J Crit Care Med, 2021)
Objective: To study the correlation between the cycle threshold (CT) of reverse transcription–polymerase chain reaction (RT–PCR) test in confirmed COVID-19 patients and the severity of disease. Background: RT–PCR test is a standard method for the diagnosis of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infections. This test is based upon the amplification of the fluorescent signal. The number of cycles that the fluorescent signal undergoes to reach the threshold is called “cycle threshold.” It is inversely related to the nucleic acid content of the sample. Patients and methods: This is a single-centered, retrospective observational study. We have included a total of 192 patients. SARS-CoV-2 infection was confirmed by the RT–PCR test. Entire data have been collected from the electronic medical records. The primary outcome was 28-day mortality, whereas the secondary outcomes were intensive care unit (ICU) admission, invasive ventilation, acute kidney injury, renal replacement therapy (RRT), shock, and COVID-19 reporting and data system (CO-RADS) score on high-resolution computed tomography of the chest, total length of stay in the hospital, and the number of ICU days and ventilator days. Results: We have calculated the mean CT value for all groups and calculated the p-value for statistical significance. For the total length of stay in the hospital and the number of ICU days and ventilator days, we applied the Pearson correlation coefficient. The p-value was statistically significant for mortality, ICU admission, and shock groups. The CT values and the length of ICU stay were inversely correlated with the statistically significant p-value. Conclusion: Low CT value is associated with increased ICU admission, high mortality, shock, and increased length of ICU stay. How to cite this article: Rajyalakshmi B, Samavedam S, Reddy PR, Aluru N. Prognostic Value of “Cycle Threshold” in Confirmed COVID-19 Patients. Indian J Crit Care Med 2021;25(3):322–326.